1999
DOI: 10.1095/biolreprod61.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Survival, and Fetal and Placental Growth Following Elevation of Maternal Estradiol Blood Concentrations in the Rat1

Abstract: High doses of estrogens cause embryonic mortality, and fetal and placental growth retardation in rats. This study addresses the physiological relevance of such findings. Estradiol benzoate (EB), by s.c. injection, or estradiol-17beta (E2), delivered by a miniosmotic pump, raised maternal E2 concentrations from only slightly above control values to 5-fold. EB (1 microgram/day) over Days 6-13, 8-13, and 11-13, and continuous infusion of E2 (15 ng/h; Days 10-13) reduced fetal survival to 0%, 0%, 22%, and 75%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Estrogen and progesterone are both essential for the initiation and maintenance of pregnancy and closely related to placental growth. Estrogen is known as an inhibitor of placental growth and its deficiency may induce placental hypertrophy [2,8]. In this study, we found that ketoconazole treatment evoked increased mitosis of trophoblasts in the labyrinth zone on GD 15 without giving any unfavorable effects on maternal condition or severe damage of trophoblasts in the labyrinth zone, although cystic dilatation of maternal sinusoids was observed.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Estrogen and progesterone are both essential for the initiation and maintenance of pregnancy and closely related to placental growth. Estrogen is known as an inhibitor of placental growth and its deficiency may induce placental hypertrophy [2,8]. In this study, we found that ketoconazole treatment evoked increased mitosis of trophoblasts in the labyrinth zone on GD 15 without giving any unfavorable effects on maternal condition or severe damage of trophoblasts in the labyrinth zone, although cystic dilatation of maternal sinusoids was observed.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, even a subtle alteration or deviation of function in the placenta induced by chemicals may lead to miscarriage and/or fetal death. Whereas, overgrowth of placentas is induced with/without fetal effects under various conditions, such as hormonal incoordination [2,8], unfavorable maternal environment, facilitating compensatory recovery of fetal-growth retardation [3,4,17,18], and others. Placental hypertrophy is also detected in the intact uterus with less than six fetuses in rats [7].…”
mentioning
confidence: 99%
“…Similarly, embryo quality was not responsible, because embryos were obtained from the same pool of donor mice, culture and transfer conditions were the same, and the embryos were randomly allocated to recipients. It is well established that preimplantation changes in the maternal environment can affect fetal development and implantation rates, such as asynchrony between the endometrium and embryo (2,47,53) or changes to the hormonal milieu (3,26). Our results show that rhFSH alters the maternal environment so that pregnancy rates are reduced and fetal development perturbed.…”
Section: Discussionmentioning
confidence: 56%
“…It has been demonstrated in several species that endogenous ovarian hormone concentrations are altered by gonadotropin stimulation (17,28,31,32), so it is likely that stimulation influences the uterus indirectly by altering estradiol and progesterone production. Changes in steroid hormone concentrations can also influence implantation rates and fetal development in the rat and sheep (3,26). Changes in the expression of steroid hormone receptors [which have been observed after gonadotropin stimulation in women (20,23,33,36)] may also influence endometrial receptivity, because they mediate cellular responses to those hormones.…”
mentioning
confidence: 99%
“…(McCarthy, 2008). In our model, we have chosen to use the estrogen, 17-b estradiol and the doses chosen are comparable to those used in other studies of sexual differentiation (Bartholomeusz et al, 1999;Patisaul et al, 2006).…”
Section: Preliminary Findings In An Animal Modelmentioning
confidence: 99%